Averaging of initial-value and multipoint problems for oscillation systems with slowly varying frequencies and deviated argument - Danylyuk, I. M.; Petryshyn, R. I.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove new theorems on the substantiation of the method of averaging over all fast variables on a segment and a semiaxis for multifrequency systems with deviated argument in slow and fast variables. An algorithm for the solution of a multipoint problem with parameters is studied, and an estimate for the difference of solutions of the original problem and the averaged problem is established.